Development of linear erosion forms under the influence of technogenic conditions - Mazaeva, O. A.; Khak, V. A. (Bulletin of the Geological Society of Greece, 2007)
The activation of linear erosion forms in the south of the Irkutsk amphitheatre was stimulated by the construction and exploitation of the Bratsk water-storage reservoir in mid-XX century. In the paper, the characteristics and interaction of natural and technogenic factors influencing the erosion process are described. The construction of reservoir gave rise to new erosion mechanisms such as karst-erosion, aeolianerosion and abrasion-erosion, which did not occur under the natural (undisturbed) conditions. The large-scale topographic maps were used for evaluation of the spatial distribution of erosion in the shore zone; the active erosion processes were observed in 16 areas of the Bratsk reservoir's shore zone; the overall erosionaffected area of the Bratsk reservoir's shore is 332.9 thousand m2.